Policy Problematic Islamic Educational Institutional In Increasing The Quality of Education - Fadlan, Achmad; elwidah, Minnah; Ridwan, Ridwan; Hakim, Lukman (International Journal of Education and Teaching Zone, 2023)
This article tells about the problems in establishing Islamic education policies as a challenge in improving the quality of education and constructive efforts in advancing education. There are several issues in the policy issues of Islamic education institutions, such as the skepticism of society, the lack of vision and mission in Islamic educational institutions, and the facilities and infrastructure that are Inadequate efforts must be made by Islamic educational institutions to overcome the problems of these educational policies, namely building public trust in officials who sit in Islamic educational institutions regarding the policies implemented by every leader in Islamic educational institutions